Organizational and curricular support and efficiency of educational and health-improving activity complexes in the physical education process of students - Olena Andrieieva; Uliana Kateryna (Kharkiv State Academy of Physical Culture, 2017)
Purpose: to develop organizational and methodological support of the activity of educational and health-improving complexes in the physical education process of students in physical education and to test its effectiveness. Material & Methods: questioning with the purpose of determining the motivation of students, their observance of a healthy lifestyle, the peculiarities of leisure activities; testing the level of theoretical knowledge of students; G. L. Apanasenko methodology (2011) to assess the level of physical health. The pedagogical experiment involved 161 students who studied at the I-IV courses of the University of the State Fiscal Service of Ukraine. Results: pedagogical conditions that determine the participation of students in extracurricular activities in physical education are revealed. Conclusion: the positive influence of the introduction of the model of the activity of educational and health-improving complexes on the degree of involvement of students in extracurricular activities has been established, in turn, has helped to raise their level of health, theoretical awareness, motivation and skills of leisure.